Suturing the City- Living Together in Congo's Urban Worlds - Filip de Boeck; Sammy Baloji (ABP Autoograph, London; Galerie Imane Fares, Paris, 2016)
The readers are taken on a tour of specific urban sites in Kinshasha and beyond, which emerge as suturing points where possibilities of collective urban action and dreams of a shared future are explored. Congolese Art, Contemporary Photography
English
Keywords: Congo; GF125 Human Ecology. Anthropogeography- Settlements- Cities. Urban geography